Is information power? Exploring the potential of analytics tools for student representatives - Rates, Diego; Gašević, Dragan (International Journal for Students as Partners, 2022)
An industrial revolution based on digital technologies and data is rapidly transforming most human activities. In the case of higher education, research on learning analytics has experienced significant expansion and evolution in only a few years. However, there is still a dearth of literature on analytics tools designed to support student representatives, which could generate growing informational and technological asymmetries in higher education. To address this critical gap, this study explored the potential key data required by student representatives for their effective participation as partners in educational improvement and the main benefits that associated analytics tools could offer. To do this, this study used a micro design ethnography and a dialogic approach with participants from a Scottish university. Findings suggest that access to data and analytics could influence the participation of the student body as egalitarian partners. These results reinforce the need for further research.